A Nitric Oxide-Responsive Transcriptional Regulator NsrR Cooperates With Lrp and CRP to Tightly Control the hmpA Gene in Vibrio vulnificus - Choi, Garam; Kim, Dukyun; Im, Hanhyeok; Choi, Sang Ho (Frontiers in Microbiology, 2021)
Nitric oxide (NO) is an important antimicrobial effector produced by the host innate immune system to counteract invading pathogens. To survive and establish a successful infection, a fulminating human pathogen Vibrio vulnificus expresses the hmpA gene encoding an NO dioxygenase in an NO-responsive manner. In this study, we identified an Rrf2-family transcriptional regulator NsrR that is predicted to contain the Fe-S cluster coordinated by three cysteine residues. Transcriptome analysis showed that NsrR controls the expression of multiple genes potentially involved in nitrosative stress responses. Particularly, NsrR acts as a strong repressor of hmpA transcription and relieves the repression of hmpA by loss of the Fe-S cluster upon exposure to NO. Notably, nsrR and hmpA are transcribed divergently, and their promoter regions overlap with each other. Molecular biological analyses revealed that NsrR directly binds to this overlapping promoter region, which is alleviated by loss of the Fe-S cluster, leading to the subsequent derepression of hmpA under nitrosative stress. We further found that a leucine-responsive regulatory protein (Lrp) negatively regulates hmpA in an NsrR-dependent manner by directly binding to the promoter region, presumably resulting in a DNA conformation change to support the NsrR repression. Meanwhile, a cyclic AMP receptor protein (CRP) positively regulates hmpA probably through repression of nsrR and lrp by directly binding to each promoter region in a sequential cascade. Altogether, this collaborative regulation of NsrR along with Lrp and CRP enables an elaborate control of hmpA transcription, contributing to survival under host-derived nitrosative stress and thereby the pathogenesis of V. vulnificus.